AESTHETIC DIMENSION OF BEDHAYA ANGLIRMENDHUNG DANCE: QUALITY OF DANCER STUDY BASED ON SERAT KRIDHWAYANGGA - Wibowo, Angga Febri; Pramutomo, R.M.; Sriyadi, Sriyadi (Jurnal Kajian Seni, 2023)
Dancers play a significant role in determining the success of a dance performance. The dancer's body serves as a medium of expression to convey the choreographer's ideas and concepts, which can be enjoyed and critiqued by the audience. Therefore, dancers are expected to possess the skill to implement forms and techniques of movement. In Javanese dance, there are various aesthetic concepts related to the quality of the dancer as a performer. The Serat Kridhwayangga expresses aesthetic concepts related to the qualification of character types and movement styles used. This article aims to present the aesthetic dimension of Bedhaya Anglirmendhung dance at Pura Mangkunegaran based on the perspective of the Serat Kridhwayangga. Through this, it is hoped to demonstrate the quality of the dancer as one of the aesthetic standards in presenting Bedhaya Anglirmendhung dance. As a cultural heritage, Bedhaya Anglirmendhung naturally possesses high aesthetic standards, one of which is the dimension of the dancer as a performer. This research adopts an ethnochoreological approach with qualitative research design. Data collection techniques mainly involve literature review. The research findings indicate that Bedhaya Anglirmendhung dance, based on the Serat Kridhwayangga, belongs to the wanodya character type with the patrap beksa pucang kanginan. The wanodya character type has normative rules related to the positions and forms of movements for the head, arms, torso, and legs. Therefore, in order to achieve aesthetic quality in the presentation of Bedhaya Anglirmendhung dance, dancers must possess the skills necessary to implement these positions and forms of movements.